Kemiripan dan Potensi Produksi Aksesi Pohpohan (Pilea trinervia Wight.) dari Beberapa Daerah di Jawa Barat - ,, Sopiana; Susila, Anas Dinurrohman; Syukur, dan Muhamad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Pohpohan (Pilea trinervia Wight.) is potential indigenous vegetable to be developed as a commercial vegetables. The objectives of this research were to observe similarity and production potential of pohpohan landraces from several areas in West Java. Result based on cluster analysis at nine similarity scale, thirteen exploration pohpohan landraces were grouped into three clusters. Clusters I consisted of Warung Loa, Tugu Selatan, Palasari, Langensari, Kayu Ambon, Lebak Muncang, Situsari, Sukalilah and Lebaksiuh. Clusters II consisted of Curug Rendeng, Argalingga and Linggarjati and clusters III was Bobojong. Result from further test using Duncan Multiple Range Test (DMRT), Warung Loa is a leading landrace because showed the best result on plant height, primary branches number, leaf width, yield per plot and plant productivity. Keywords: Cluster analysis, exploration, indigenous vegetable